Code Switching in the Things Left Behind Novel By Kim Sae Byoul and Jeon Ae Won - Gede Kediri Suryadharma, Gede Kediri Suryadharma (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
Code switching is a prevalent sociolinguistic phenomenon observed in various communication settings, including literary works. This study explores the occurrence of code switching in the novel